Liming enhances longevity of wheat seeds produced in acid soils - da Silva, Tiago Alexandre [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; Batista, Thiago Barbosa [UNESP]; Bossolani, João William [UNESP]; de Oliveira, Gustavo Roberto Fonseca [UNESP]; Basso, Denise Puntel [UNESP]; de Almeida Carmeis Filho, Antônio Carlos [UNESP]; Bravo, Juliana Pereira [UNESP]; da Silva, Edvaldo Aparecido Amaral [UNESP] (Springer Nature, 2022)
The environment where plants grow, such as acidic soils, interferes with the nutrient concentration and physiological quality of seeds. This hypothesis was tested using wheat seeds as a model crop, grown in a tropical soil with and without lime application for twelve years. Here we show that lime provides remarkable enhancements in soil chemistry and seed composition, without altering the seed’s germination and vigor. Also, it favors the production of seeds with additional molecular mechanisms that extend their longevity. Our results indicate that the application of lime mitigates acidity in tropical soils and ensures the production of seeds with enhanced chemical composition and longer life span.